Current situation and issues regarding termination of risk management plans in Japan - Kameyama, Natsuko; Hosaka, Aoi; Maeda, Hideki (Frontiers in Medicine, 2024)
In Japan, drugs approved after the 2013 implementation of the risk management plan (RMP) have the opportunity to be evaluated for RMP termination. However, the guidelines for risk management following the termination of an RMP remain unclear. Drugs are evaluated for RMP termination at the timing of reexamination. Reexamination system is unique to Japan and initiated in 1979, verifies the approved efficacy and safety of a newly marketed drug based on the data from its actual use over a certain period. This study investigated drugs in Japan for which the RMP requirement was lifted upon reexamination and those for which it was not. We organized their characteristics and considered future issues. From April 2013 to March 2023, 72 drugs with RMPs completed reexamination in Japan. The RMP requirement was lifted for 69 drugs (95.8%) and remained for three drugs (4.2%). Upon RMP termination, 16 out of 69 drugs (23.2%) had important potential risks not listed in the package insert, with malignant neoplasm being the most common. Eleven drugs (15.9%) had important missing information not listed in the package insert, with the most common being the impact on cardiovascular risk. Two drugs (2.9%) had ongoing additional pharmacovigilance activities, and 43 drugs (62.3%) had additional risk minimization activities. Upon reexamination completion, the RMP requirement was lifted for many drugs and remained for a few. Should safety concerns require continued attention following reexamination, we advocate for the continuation of the RMP, guided by more explicit rules. In light of the harmonization of RMP rules with those of other countries, there is a desire for enhanced drug safety management.